Balance performance in children with borderline intellectual functioning and specific language impairment - Kaupuzs, Aivars; Larins, Viesturs (Social Welfare: Interdisciplinary Approach, 2017)
The balance is one of the substantial motor skills that ensure development of normal movement patterns. There are limited body of research on motor performance in children with borderline intellectual functioning (BIF) that manifesting as cognitive and behavioural problems and specific language impairment (SLI) that is a developmental disorder involving delayed language. The aim of the research is to find the differences of vestibular system indicators in specific groups. The balance Sway Index (SI) was tested by digital platform BioSway using the m-CTSIB test in four conditions. The research group included participants at 11-13 years age who are enrolled in special schools. The normative data of m-CTSIB test were gained in previous researches. The findings show that boys exhibited greater SI than girls. Children with disorders demonstrated significantly lower balance performance in two test positions in each group. Participants with BIF had significantly higher SI than typically developing peers in two test positions with eyes open. Children with SLI had significantly higher SI accordingly in two test positions on firm surface respectively eyes open and eyes closed. The findings suggest that mechanism of vestibular adaptation in challenging environments differ with disorder diagnosis
Keywords: balance; BioSway; borderline intellectual functioning; children; specific language impairment